Character Adaptations: Recurrence and Return. (21st August 2020) - Strong, Jeremy
Abstract: This paper examines recurring character storytelling as the most prodigiously successful tradition in fiction of the last two hundred years. James Fenimore Cooper's Leatherstocking Tales and Honoré de Balzac's La Comédie humaine are proposed as significant precursors that embody two dominant trends within recurring character storytelling: the central protagonist series and the populous storyworld. The foundations of recurring character storytelling are traced in a range of determinants including: increasing literacy and the rise of popular genres; modes of serial publication; and the development and enforcement of copyright law. Finally, focusing upon the central protagonist variant, the age and aging of recurring characters are discussed as a necessary consideration for the makers and adapters of such series. Several are analysed, including James Bond, Sharpe, the Morse franchise, and Midsomer Murders, to illuminate how makers handle chronology, the passage of time, and related issues in adaptation. As part of an assessment of the 'affordances' of recurring character fictions, nostalgia and familiarity are discussed as significant dimensions of the experience they furnish.